Alien race : visual development of an intergalactic adventure. - Robertson, Scott, 1966- (Culver City : Designstudio, 2009)
Alien Race is an illustrated narrative of an original science fiction tale. Three Art Center College of Design entertainment design students discuss the process of and develop the visuals for one of the most unique stories today - combining action, adventure and captivating art to introduce the reader to the fascinating world of concept design.